PENGARUH KOMPOS DAUN KEMIRI SUNAN (Reutealis trisperma (Blanco) Airy Shaw) TERHADAP KESUBURAN ENTISOL - Andarini Puspita; Budi Santoso; Syahrul Kurniawan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Leaves of Reutealis trisperma (locally known as kemiri Sunan) are potential sources of organic matter and improve soil fertility, especially by increasing soil nutrient availability. This study aimed to analyze the impact of the application of compost using kemiri Sunan leaves as raw material on soil fertility, such as pH, total N and soil organic C. This study used a completely randomized design with six treatments and four replications. The treatments were without compost (control), compost 4 t ha-1, compost 8 t ha-1, compost 12 t ha-1, compost 16 t ha-1 and compost 20 t ha-1. This study used a PVC pipe with a diameter of 14 cm and a height of 60 cm for the composting process and using polybags for the soil incubation process. The leaves were mixed with EM4, molasses, and water in a ratio of 1:1:50; after mixing, all the ingredients were put into a tube, and observations were made. The soil was then mixed with compost according to the treatment dose of compost 0; 4; 8; 12; 16; 20 t ha-1, then added water until it reached field capacity and then put into a polybag and incubated for 30 days. Observations were made at 0, 15, and 30 days after incubation. The results of this study showed that the application of waste compost of kemiri Sunan leaves had a significantly increased soil pH, total N, and organic C. The best application of kemiri Sunan leaf compost was found at a dose of 20 t ha-1 .